Screening kinase inhibitors identifies MELK as a prime target against influenza virus infections through inhibition of viral mRNA splicing - Yang, Xuanye; Feng, Xili; Liu, Qianyun; An, Lele; Ma, Zhongren; Ma, Xiaoxia (Frontiers in Microbiology, 2025)
Influenza epidemics represent a significant threat to global public health, primarily caused by the influenza viruses A and B. Although antiviral drugs targeting the influenza virus, such as zanamivir and oseltamivir, are clinically available, the emergence of virus evolution and drug resistance necessitates the development of host-directed therapies. Protein kinases are essential components of host signaling pathways, including the orchestration of virus–host interactions. By screening a library of kinase inhibitors, we identified that OTS167, a pharmacological inhibitor of maternal embryonic leucine zipper kinase (MELK), strongly inhibits the infections caused by multiple influenza virus subtypes in cell culture. This antiviral activity was further confirmed by treatment with another MELK pharmacological inhibitor, MELK-8a, and siRNA-mediated MELK gene silencing. In mice challenged with the influenza A virus, treatment with OTS167 inhibited both viral replication and lung inflammation. Mechanistically, inhibition of MELK by OTS167 downregulates the downstream effector CDK1, thereby inhibiting influenza virus M1 mRNA splicing to reduce viral replication and virus particle assembly. Finally, we demonstrated that combining OTS167 with zanamivir or oseltamivir resulted in additive antiviral activity. In conclusion, we identified MELK as a crucial host kinase that supports the influenza virus infection. OTS167, a pharmacological inhibitor of MELK currently undergoing phase II clinical trials for treating cancer, potently inhibits influenza virus infections in vitro and in mice, representing a promising lead for developing novel influenza antivirals.